Eco-Islamic Boarding School Waste Management: A Systematic Literature Review Approach - Riskawati, Reni (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
The eco-Islamic boarding school program is a model of Islamic boarding school-based environmental education that is still developing in various places in Indonesia. The aim of this research is to obtain information regarding the management of eco-Islamic boarding school waste. Systematic Literature Review is the method used in this research. The results of this eco-Islamic boarding school research are used to minimize waste going to final landfills. Through environmentally friendly and sustainable infrastructure, environmental quality will be improved